Konsep Dasar Manajemen Akademik di Perguruan Tinggi Islam - Indra Agus Salam; Muhammad Syaifuddin; Syafaruddin (STAI Terpadu Yogyakarta, 2023)
Academic management in Higher Education plays a very important role in improving academic services. Effective and efficient academic planning, implementation and supervision will result in a productive work system. The purpose of this study is to find out the concept of academic planning starting from the basic concepts and objectives of academic implementation. The research method used is a descriptive method with a qualitative approach. The data collection technique used in this study is a literature study, by collecting relevant data from books, dictionaries, journals, magazines, and so on without having to conduct a field review. The result of this study is that management must be applied in an effort to organize teaching and learning activities because by applying management aspects such as planning, organizing, controlling, and evaluation so that educational implementation activities can run in a planned, systematic, sustainable manner and achieve the goals that have been created to achieve the quality standards of higher education education.